The COlorectal NEoplasia Endoscopic Classification to Choose the Treatment classification for identification of large laterally spreading lesions lacking submucosal carcinomas: A prospective study of 663 lesions. Issue 1 (28th January 2022) - Brule, Clementine; Pioche, Mathieu; Albouys, Jeremie; Rivory, Jerome; Geyl, Sophie; Legros, Romain; Rostain, Florian; Dahan, Martin; Lepetit, Hugo; Sautereau, Denis; Ponchon, Thierry; Auditeau, Emilie; et al.
Abstract: Introduction: Optical diagnosis is necessary when selecting the resection modality for large superficial colorectal lesions. The CO lorectal NE oplasia Endoscopic C lassification to C hoose the T reatment (CONECCT) encompasses overt (irregular pit or vascular pattern) and covert (macroscopic features) signs of carcinoma in an all‐in‐one classification using validated criteria. The CONECCT IIC subtype corresponds to adenomas with a high risk of superficial carcinoma that should be resected en bloc with free margins. Methods: This prospective multicentre study investigated the diagnostic accuracy of the CONECCT classification for predicting submucosal invasion in colorectal lesions >20 mm. Optical diagnosis before en bloc resection by endoscopic submucosal dissection (ESD) was compared with the final histological diagnosis. Diagnostic accuracy for the CONECCT IIC subtype was compared with literature‐validated features of concern considered to be risk factors for submucosal invasion (non‐granular large spreading tumour [NG LST], macronodule >1 cm, SANO IIIA area, and Paris 0‐IIC area). Results: Six hundred 63 lesions removed by ESD were assessed. The en bloc, R0, and curative resection rates were respectively 96%, 85%, and 81%. The CONECCT classification had a sensitivity (Se) of 100%, specificity (Sp) of 26.2%, positive predictive value of 11.6%, and negative predictive value (NPV) of 100% for predicting at least submucosal adenocarcinoma. The sensitivity of CONECCT IIC (100%) to predict submucosal cancer was superior to all other criteria evaluated. COlorectal NEoplasia Endoscopic Classification to Choose the Treatment IIC lesions constituted 11.5% of all submucosal carcinomas. Conclusion: The CONECCT classification, which combines covert and overt signs of carcinoma, identifies with very perfect sensitivity (Se 100%, NPV 100%) the 30% of low‐risk adenomas in large laterally spreading lesions treatable by piecemeal endoscopic mucosal resection or ESD according to expertise without undertreatment. However, the low specificity of CONECCT leads to a large number of potentially not indicated ESDs for suspected high‐risk lesions.